Novel nitrogen-doped carbon dots prepared under microwave-irradiation for highly sensitive detection of mercury ions. Issue 4 (April 2020) - Ghanem, Ali; Al-Qassar Bani Al-Marjeh, Rama; Atassi, Yomen
Abstract: In this paper, new nitrogen doped carbon dots with a high quantum yield and novel optical properties were synthesized by a simple and fast one step microwave-assisted synthesis. Citric acid monohydrate was used as a carbon source and 2, 2-dimethyl-1, 3-propanediamine as nitrogen source. The prepared N-CDs were characterized by Fourier transform infrared, Raman, UV-visible and photoluminescence spectroscopies. Transmission electron microscope (TEM) images revealed that the N-CDs have distinctive flake-shape morphology. The N-CDs exhibit bright blue luminescence and quenching response towards Hg 2+ ions. The quenching sensitivity was investigated. The results indicate a limit of detection as low as 7.63 nM and a linear relationship over the range 0–4.2 μM. In addition, the prepared N-CDs were tested as sensor for pH in the range from 1 to 7. Abstract : Analytical chemistry; Environmental Science; carbon dots; Hg 2+ detection; Photoluminescence; pH sensing; LOD